Prognostic significance of the preoperative lymphocyte to C‐reactive protein ratio in patients with stage III colorectal cancer. Issue 10 (2nd July 2022) - Eren, Tunc
Abstract: Background: Stage III colorectal cancer (CRC), which accounts for approximately one third of all CRC cases, is associated with worsened prognosis. The aim of this study was to compare the preoperatively measured systemic inflammatory markers and to define the most significant marker in terms of its prognostic value in stage III CRC. Methods: Surgically treated stage III CRC patients were included. Demographics, preoperatively measured Glasgow prognostic score (GPS), neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), lymphocyte/C‐reactive protein ratio (LCR) and C‐reactive protein/albumin ratio (CAR) values, clinicopathological features, surgical, oncological and survival outcomes were recorded and statistically analysed. Results: The study group of 102 patients consisted of 65 (63.7%) men and 37 (36.3%) women with a median age of 64 (range: 26–89). The mean follow‐up period was 42.8 ± 30.5 (range: 6–107) months. Overall survival (OS) and disease‐free survival (DFS) rates were 71.6%, and 67.7%, respectively. Elevated CRP, GPS 2, LCR ≤ 0.530, CAR ≥ 0.080, higher numbers of metastatic lymph nodes and N2b nodal status were detected to impair DFS ( P  = 0.001, P  = 0.015, P  = 0.001, P  = 0.001, P  = 0.001 and P  = 0.043, respectively). Variables including GPS 2, PLR≥190.83, CAR≥0.045, LCR≤0.684, surgical site infection and longer hospital stay decreased OS ( P  = 0.004, P  = 0.002, P  = 0.005, P  = 0.001, P  = 0.001 and P  = 0.001, respectively). According to multivariate analysis; PLR ≥ 190.83 was associated with three times [HR: 2.892 (95% CI: 1.100–7.602), P  = 0.031], and LCR ≤ 0.684 was associated with four times [HR: 3.919 (95% CI: 1.130–13.592), P  = 0.031] greater risk of cancer‐related mortality. Conclusion: As an independent prognostic factor, LCR had the highest impact on predicting survival after curative resection for stage III CRC. Abstract : Stage III colorectal cancer (CRC), which accounts for approximately one third of all CRC cases, is associated with worsened prognosis. The aim of this study was to compare the preoperatively measured systemic inflammatory markers and to define the most significant marker in terms of its prognostic value in stage III CRC. As an independent prognostic factor, lymphocyte/C‐reactive protein ratio (LCR) had the highest impact on predicting survival after curative resection for stage III CRC.